Politeness forms in the Russian and Chinese linguoculture: linguopragmatic aspect (Eurasian Journal of Philology Science and Education, 2019)
In the article questions of crosscultural communication on material of language realization of manifestation of politeness in the Chinese and Russian cultures are considered. The politeness is a symbolof a human civilization and important criterion of human public work. Apology acts as one of the mostimportant types of politeness. We live in the real world, in this world every day we meet different situations and different difficulties. The person quite often should apologize for something to people around,along with it the person appears in a situation of the accepting apology. And usually it happens to thehelp of language. Language as the major means of communication and the public phenomenon is themost important weapon of activity of the person in general. And it relates to all languages, to all cultures.In crosscultural communication of both parties of the procedure of apology usually happens to use offormulas of speech etiquette, and each people have principles and ways of expression of apology. In thepresent article features of speech forms of apology in the Russian and Chinese linguoculture are investigated, the comparative analysis of two languages for identification in them of similarities and differencesin apology expression is carried out.